Efficient Solid‐State Light‐Emitting CuCdS Nanocrystals Synthesized in Air1. Issue 9 (16th January 2015) - Khan, Ali Hossain; Dalui, Amit; Mukherjee, Soham; Segre, Carlo U.; Sarma, D. D.; Acharya, Somobrata
Abstract Semiconductor nanocrystals (NCs) possess high photoluminescence (PL) typically in the solution phase. In contrary, PL rapidly quenches in the solid state. Efficient solid state luminescence can be achieved by inducing a large Stokes shift. Here we report on a novel synthesis of compositionally controlled CuCdS NCs in air avoiding the usual complexity of using inert atmosphere. These NCs show long‐range color tunability over the entire visible range with a remarkable Stokes shift up to about 1.25 eV. Overcoating the NCs leads to a high solid‐state PL quantum yield (QY) of ca. 55 % measured by using an integrating sphere. Unique charge carrier recombination mechanisms have been recognized from the NCs, which are correlated to the internal NC structure probed by using extended X‐ray absorption fine structure (EXAFS) spectroscopy. EXAFS measurements show a Cu‐rich surface and Cd‐rich interior with 46 % CuI being randomly distributed within 84 % of the NC volume creating additional transition states for PL. Color‐tunable solid‐state luminescence remains stable in air enabling fabrication of light‐emitting diodes (LEDs).